1999
DOI: 10.1038/sj.bjp.0702682
|View full text |Cite
|
Sign up to set email alerts
|

Spinal effect of a neuropeptide FF analogue on hyperalgesia and morphine‐induced analgesia in mononeuropathic and diabetic rats

Abstract: 1 1DMe, a neuropeptide FF (NPFF) analogue, has been shown to produce antinociception and to enhance morphine analgesia in rats after intrathecal administration. To determine whether 1DMe could correct hyperalgesia and restore morphine e cacy in mononeuropathic (MN) and diabetic (D) rats we examined the spinal e ect of 1DMe in MN and D rats without and after spinal blockade of m-and d-opioid receptors with CTOP and naltrindole, respectively. The in¯uence of 1DMe on morphine-induced antinociception was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 49 publications
(75 reference statements)
2
14
0
Order By: Relevance
“…In contrast to ICV injection, intrathecally applied NPFF induces a long lasting naloxone reversible analgesia in both thermal and mechanical tests and, furthermore, NPFF at subeffective doses can potentiate morphine analgesia (Gouarderes et al, 1993). Following this very first report on the antinociceptive activity of NPFF, some additional studies have confirmed this observation in normal rats and in rats with inflammatory or neuropathic pain, for both NPFF or its analogues (Altier et al, 2000;Courteix et al, 1999;Gouarderes et al, 1996a;Gouarderes et al, 1993). A qualitatively similar but more potent effect was observed for the NPFF analogue D-Tyr 1 ,(NMe)Phe 3 -NPFF.…”
Section: Pain and Morphine Modulating Activities And Receptor Bindingsupporting
confidence: 48%
See 1 more Smart Citation
“…In contrast to ICV injection, intrathecally applied NPFF induces a long lasting naloxone reversible analgesia in both thermal and mechanical tests and, furthermore, NPFF at subeffective doses can potentiate morphine analgesia (Gouarderes et al, 1993). Following this very first report on the antinociceptive activity of NPFF, some additional studies have confirmed this observation in normal rats and in rats with inflammatory or neuropathic pain, for both NPFF or its analogues (Altier et al, 2000;Courteix et al, 1999;Gouarderes et al, 1996a;Gouarderes et al, 1993). A qualitatively similar but more potent effect was observed for the NPFF analogue D-Tyr 1 ,(NMe)Phe 3 -NPFF.…”
Section: Pain and Morphine Modulating Activities And Receptor Bindingsupporting
confidence: 48%
“…In other studies (Altier et al, 2000;Courteix et al, 1999), intrathecal injections of NPFF were found to have no effect on acute thermal or mechanical pain in normal rats; whereas in rats with inflammatory or neuropathic pain, a potent antiallodynic effect was observed. It seems that the antinociceptive effect of NPFF or its analogue, D-Tyr 1 ,(NMe)Phe…”
Section: Pain and Morphine Modulating Activities And Receptor Bindingmentioning
confidence: 99%
“…In the rat intestine, no NPFF immunoreactivity was seen in the autonomic nervous system or endocrine cells (23). Interestingly, recent investigations have indicated that NPFF can function as an endogenous anti-opioid agent or a pro-opioid agent depending on the animal species (24). There are also species differences in the distribution of NPFF receptors between the human and rat (19).…”
Section: Discussionmentioning
confidence: 89%
“…5 mg/rat, and 0.75 mg/rat) [22,23] and four other groups received NMDA receptor antagonist MK801 (0.25 mg/rat, 0.5 mg/rat, 0.75 mg/rat, and 1 mg/rat) [22] and were compared with saline control group. Experiment 2: effects of d-opioid receptor agonist and antagonist on anxiety-like behavior Four groups of rats received bilateral dorsal hippocampus injection (intra-CA1) of selective d receptor agonist enkephalin (1 mg/rat, 2 mg/rat, 5 mg/rat, and 10 mg/rat) [24,25], and four other groups received d receptor antagonist naltrindole hydrochloride (0.25 mg/rat, 0.5 mg/rat, 1 mg/rat, and 2 mg/ratdintra-CA1) [26,27]. These rats were thereafter compared with a saline control group.…”
Section: Drugsmentioning
confidence: 99%